2010
DOI: 10.1177/1753465810384606
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gastroesophageal reflux and asthma: an update

Abstract: Asthma and gastroesophageal reflux disease (GERD) are both common conditions and, hence, they often coexist. However, asthmatics have been found to have a much greater prevalence of GERD symptoms than the general population. There remains debate regarding the underlying physiologic mechanism(s) of this relationship and whether treatment of GERD actually translates into improved asthma outcomes. Based on smaller trials with somewhat conflicting results regarding improved asthma control with treatment of GERD, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 43 publications
1
35
0
1
Order By: Relevance
“…In the absence of a response to saline irrigation with or without topical corticosteroids and/or anti-histamines, a computerized tomography (CT) scan of the sinuses and a referral to a dedicated Ear, Nose and Throat physician should be considered. GERD occurs in nearly 80% of all individuals with asthma 16 but despite this high prevalence, empiric treatment of all asthma patients with a proton pump inhibitor has not proven to be effective in decreasing asthma exacerbations. 16 If nocturnal cough remains a predominant asthma symptom despite the absence of overt reflux, a 24 hour esophageal pH monitoring may identify previously unrecognized GERD.…”
Section: Summary Of Evidence and Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a response to saline irrigation with or without topical corticosteroids and/or anti-histamines, a computerized tomography (CT) scan of the sinuses and a referral to a dedicated Ear, Nose and Throat physician should be considered. GERD occurs in nearly 80% of all individuals with asthma 16 but despite this high prevalence, empiric treatment of all asthma patients with a proton pump inhibitor has not proven to be effective in decreasing asthma exacerbations. 16 If nocturnal cough remains a predominant asthma symptom despite the absence of overt reflux, a 24 hour esophageal pH monitoring may identify previously unrecognized GERD.…”
Section: Summary Of Evidence and Key Messagesmentioning
confidence: 99%
“…GERD occurs in nearly 80% of all individuals with asthma 16 but despite this high prevalence, empiric treatment of all asthma patients with a proton pump inhibitor has not proven to be effective in decreasing asthma exacerbations. 16 If nocturnal cough remains a predominant asthma symptom despite the absence of overt reflux, a 24 hour esophageal pH monitoring may identify previously unrecognized GERD. Upper gastrointestinal endoscopy should be considered in individuals with eosinophilia and suspected of having eosinophilic esophagitis.…”
Section: Summary Of Evidence and Key Messagesmentioning
confidence: 99%
“…Gastroesophageal reflux disease could worsen asthma either by direct effects on airway responsiveness or via aspiration-induced inflammation [84]. Conversely, the bronchoconstriction observed in…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…However, inconsistent results have been obtained in several studies on the effects of treatment of GERD on asthma outcomes [84,85]. In 2003, a Cochrane systematic review of the available literature examining the effect of GERD treatment for asthma showed that antireflux therapy did not consistently improve lung function, asthma symptoms, nocturnal asthma or the use of asthma medications [86].…”
Section: Reviewmentioning
confidence: 99%
“…The authors write that current available data has shown limited benefit of treatment in symptomatic gastroesophageal reflux disease (GERD) with asthma and no clear benefit of asthma control. Reviewed data suggests empirical treatment of asymptomatic GERD in asthmatics is not a useful practice; instead, the clinician should focus on other factors which can affect asthma control [McCallister et al 2011]. …”
mentioning
confidence: 99%